The effect of specific therapeutic agents on inflammation in sepsis-induced neonatal rats - Ilhan, Nevin; Gul, Huseyin Fatih; Susam, Solmaz; Ilhan, Necip; Bardas, Ruken (Walter de Gruyter Gmbh, 2020)
Objective: The aim of this study was to investigate the effect of Thalidomide and Etanercept on inflammation parameters in a neonatal rat sepsis model induced with Lipopolysaccharide (LPS). Materials and methods: Four-week-old male Wistar Albino rats were used in the experiment. LPS (5 mg/kg) was administered to rats as sepsis-inducing agent and two anti-inflammatory drugs, Thalidomide and Etanercept were given intraperitoneally as chemotherapeutic agents. The septic neonatal rats were treated with Thalidomide (0.5 mg/kg), Etanercept (1 mg/kg), and a combination of the two. All therapeutic agents were injected half an hour after injecting LPS. It took 24 h to perform the entire experiment. Whereupon, liver tissues of the animals were removed, presepsin of liver tissue and NF-kappa B levels were measured by ELISA analysis and NF-kappa B protein expression levels were determined by Western blotting. Results: A significant increase was detected in presepsin and NF-kappa B levels in LPS group compared to sham and treatment groups. In Western Blot evaluations, there was a significant decrease in the expression of NF-kappa B protein in treatment groups compared to sepsis group. Conclusions: It was observed that Thalidomide and Etanercept had potential effects on the treatment of neonatal sepsis.
Sepsis oluşturulmuş neonatal siçanlarda spesifik terapötik ajanlarin inflamasyon üzerindeki etkisi
Keywords: Sepsis; Presepsin; NF-kappa B; Thalidomide; Etanercept